Characterisation of microvascular abnormalities using OCT angiography in patients with biallelic variants in USH2A and MYO7A. Issue 4 (2nd July 2019) - Hagag, Ahmed M; Mitsios, Andreas; Gill, Jasdeep S; Nunez Do Rio, Joan M; Theofylaktopoulos, Vasileios; Houston, Sarah; Webster, Andrew R; Dubis, Adam M; Moosajee, Mariya
Abstract : Aims: Using optical coherence tomography angiography (OCTA) to characterise microvascular changes in the retinal plexuses and choriocapillaris (CC) of patients with MYO7A and USH2A mutations and correlate with genotype, retinal structure and function. Methods: Twenty-seven patients with molecularly confirmed USH2A (n=21) and MYO7A (n=6) mutations underwent macular 6×6 mm OCTA using the AngioVue. Heidelberg spectral-domain OCT scans and MAIA microperimetry were also performed, the preserved ellipsoid zone (EZ) band width and mean macular sensitivity (MS) were recorded. OCTA of the inner retina, superficial capillary plexus (SCP), deep capillary plexus (DCP) and CC were analysed. Vessel density (VD) was calculated from the en face OCT angiograms of retinal circulation. Results: Forty-eight eyes with either USH2A (n=37, mean age: 34.4±12.2 years) or MYO7A (n=11, mean age: 37.1±12.4 years), and 35 eyes from 18 age-matched healthy participants were included. VD was significantly decreased in the retinal circulation of patients with USH2A and MYO7A mutations compared with controls (p<0.001). Changes were observed in both the SCP and DCP, but no differences in retinal perfusion were detected between USH2A and MYO7A groups. No vascular defects were detected in CC of the USH2A group, but peripheral defects were detected in older MYO7A patients from the fourth decade of life. VD in the DCP showed strong association with MS and EZ width (Spearman's rho =0.64 and 0.59, respectively, p<0.001). Conclusion: OCTA was able to detect similar retinal microvascular changes in patients with USH2A and MYO7A mutations. The CC was generally affected in MYO7A mutations. OCT angiography may further enhance our understanding of inherited eye diseases and their phenotype-genotype associations.